Manito Park [videorecording (DVD)] : a reflection of Spokane's past - Briley, Robin; Bolser, Jim; Brown, Richard; Bamonte, Suzanne; Bamonte, Tony, 1942- (Peak Video Productions, 2004)
Presents the history of Spokane, Washington's Manito Park.